The Porter hypothesis and the economic consequences of environmental regulation : A neo-Schumpeterian approach - Roediger-Schluga, Thomas (Cheltenham, UK ; Northampton, MA : Edward Elgar Pub., 2004)
Discusses innovation impacts and techno-economic consequences of environmental regulation.
Includes bibliographical references (p. 310-337) and index.
rpm 09/09/16
Loans
Keywords: Environmental economics; Environmental policy; Ecological engineering